Reducing Capacity, Chlorogenic Acid Content and Biological Activity in a Collection of Scarlet (Solanum aethiopicum) and Gboma (S. macrocarpon) Eggplants - Plazas, Mariola (Int J Mol Sci, 2014)
Scarlet (Solanum aethiopicum) and gboma (S. macrocarpon) eggplants are important vegetables in Sub-Saharan Africa. Few studies have been made on these crops regarding the diversity of phenolic content and their biological activity. We have studied the reducing activity, the chlorogenic acid and other phenolic acid contents in a collection of 56 accessions of scarlet eggplant, including the four cultivated groups (Aculeatum, Gilo, Kumba, Shum) and the weedy intermediate S. aethiopicum-S. anguivi types, as well as in eight accessions of gboma eggplant, including the cultivated S. macrocarpon and its wild ancestor, S. dasyphyllum. A sample of the accessions evaluated in this collection has been tested for inhibition of nitric oxide (NO) using macrophage cell cultures. The results show that there is a great diversity in both crops for reducing activity, chlorogenic acid content and chlorogenic acid peak area (% of total phenolic acids). Heritability (H(2)) for these traits was intermediate to high in both crops. In all samples, chlorogenic acid was the major phenolic acid and accounted for more than 50% of the chromatogram peak area. Considerable differences were found among and within groups for these traits, but the greatest values for total phenolics and chlorogenic acid content were found in S. dasyphyllum. In most groups, reducing activity was positively correlated (with values of up to 0.904 in the Aculeatum group) with chlorogenic acid content. Inhibition of NO was greatest in samples having a high chlorogenic acid content. The results show that both crops are a relevant source of chlorogenic acid and other phenolic acids. The high diversity found also indicates that there are good prospects for breeding new scarlet and gboma eggplant cultivars with improved content in phenolics and bioactive properties.